Faktor – Faktor Pemicu Terjadinya Kesalahan Sistem Informasi Manajemen Terhadap Realisasi Penerimaan Puskesmas “X” - Faris Rahmawan; Tituk Diah Widajantie (Institut Nalanda, 2023)
The management information system at the Puskesmas is the latest breakthrough in increasing the effectiveness of health services, and one of them is information on acceptance at the Puskesmas. This study aims to reveal the triggers for the occurrence of management information system errors on the realization of acceptance at the Pukesmas